Case report: Detection of maxillary sinusitis with inverted impacted teeth using Cone-beam Computed Tomography - Damayanti, Merry Annisa; Dhiaulhaq, Rifarana Inayah; Muchlis, Muhammad Rakhmat Ersyad; Epsilawati, Lusi; Sam, Belly; Pramanik, Farina; Lita, Yurika Ambar (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: The aim of this case report is to describe radiographically the specific features of maxillary sinusitis on CBCT radiograph. Case Report: A 20-year-old female patient came to RSGM UNPAD with a consul letter from Oral Surgery specialist for a CBCT radiography examination to see impacted teeth. The results showed radiointermediate images in the maxillary sinus which showed thickening of the sinus mucosa and an inverted impacted teeth on the right maxillary. Conclusion: Maxillary sinusitis could be assessed using extra oral radiography and CBCT. CBCT examination was used in determining the source of the lesion, the extent of the lesion, and the thickness of the maxillary sinus mucosa.